Netiquette of using internet - Rasulov, Xushnud (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Nowadays, in the world of information, the era of the Internet, the rapid development of multi-media information technology such asInternet TV, Internet radio, email, online video, and their audience and influence are expanding.There is no need to talk too much. Suchinformationthe tools of the young people with a great deal of interest, and from themIsak, which is widely used, is really itit is difficult to understand the importance of the matter